Laptop, livestock drawings and ricewine: A demand analysis for livestock insurance in Northern Vietnam - Isabel Fischer; Gertrud Buchenrieder (Savings and Development, 2009)
Livestock plays a pivotal role for smallholder production systems in mountainous Northern Vietnam. Economic risks, especially the loss of livestock, are major reasons for slipping into poverty. Normally, insurance systems could step in to assist. In developing countries however, insurance markets are usually underdeveloped. For this study, field research on livestock insurance was carried out. We employed novel interactive computing tools and implemented an Adaptative Conjoint Analysis (ACA). One hundred and fifty five (155) farm households of different ethnic minority groups in Northern Vietnam contributed to the study. The pros and cons of livestock insurance are discussed and policy recommendations are presented to improve the overall situation of vulnerable households in mountainous Northern Vietnam. – – Dans les régions montagneuses au nord du Vietnam, le bétail joue un rôle central pour les petits propriétaires d'exploitations agricoles. Les risques économiques, particulièrement de perte de bétail, sont parmi les facteurs majeurs menant à la pauvreté. Habituellement, les systèmes d'assurances interviennent alors. Cependant, dans les pays en développement, ces systèmes sont encore souvent précaires. Pour cet article, une enquête de terrain utilisant des outils informatiques interactifs a été réalisée, permettant l'Analyse Conjointe Adaptative (ACA) des réponses de 155 ménages appartenant à différentes minorités ethniques des provinces de Son La et Ban Kan. Sur cette base, les options de recours à l'assurance sont examinées et les avantages et inconvénients d'assurer le bétail, discutés. Des recommandations politiques sont avancées contribuant à améliorer la situation des ménages vulnérables dans les régions concernées par l'étude.
Keywords: Q14; Q16; R22; 330; livestock insurance; adaptive conjoint analysis (ACA); risk management; Vietnam